Effect of Platen Restraint on Stress–Strain Behavior of Concrete under Uniaxial Compression: A Comparative Study - Kumar, S.; Mukhopadhyay, T.; Waseem, S.A.; Singh, B.; Iqbala, M.A. (Проблемы прочности, 2016)
The stress-strain model of concrete depends on the degree of frictional resistance across the loading surfaces of a test specimen depending on the antifriction medium used during testing. This article presents a comparative study of platen restraint on the behavior of concrete under uniaxial compression based on an experimental investigation. The effect of four commercially available antifriction media (neoprene, polyvinyl chloride, teflon, and grease) with different layer thicknesses on platen restraint have been studied for a normal strength concrete and a relatively high-strength concrete. Subsequently, the effect of platen restraint has been quantified using the analogy of toughness. The experimental results indicate that post-ultimate response of concrete is significantly affected by platen restraint. It is shown that the stress–strain curve obtained from a conventional uniaxial compression test not only describes specimen/material behavior but also represents interaction between specimen and loading platen. Among the four antifriction media used in this investigation, grease is the most effective in reducing frictional resistance. Failure patterns of the concrete specimens for different antifriction media are also subsequently analyzed.